The Information Needs of Canadian Midwives and Their Evidence Informed Practices: A Canada-Wide Survey - Barnes, Lindsay; Freund, Luanne; Giustini, Dean (Evidence Based Library and Information Practice, 2020)
Objective – The study aim was to understand the extent to which Canadian registered midwives have access to and make use of clinically relevant information for evidence based midwifery practice.Methods – A survey instrument was created consisting of 17 multiple choice, matrix table, and short answer questions and distributed to 1,690 recipients on the Canadian Association of Midwives email list in fall 2018. In total, 193 responses were included in the analysis.Results – One third of midwives do not have library memberships. Midwives reported that limited access to clinically relevant information is a key challenge in applying information in practice. Midwives with library memberships reported more frequent use of high-quality information while midwives without memberships reported more frequent use of websites. Midwives with advanced degrees (graduate, PhDs) were more likely to be high-frequency information users and rank themselves higher on evidence based competency scales than their undergraduate-holding colleagues. Clinical practice guidelines were important information sources and used frequently by midwives.Conclusion – Midwives reported low levels of academic or hospital library memberships and yet used information frequently. Clinical practice guidelines support the work of midwives but are inaccessible to some due to paywalls. Midwives lacked confidence in evidence based practice and reported critical appraisal as an area for development. Solutions to these problems could be addressed at the hospital, health authority, provincial, or national association level, or within midwifery departments at Canadian universities. Hospital and academic libraries should prioritize the information needs of students and practicing midwives and identify ways to foster use of library resources through administrative or educational interventions.